Evaluation of surgical outcomes of arthroscopic subtalar arthrodesis performed through two lateral portals - Villela, Rafael Freitas; Magalhães, João Murilo Brandão; Gomes, Rogério de Andrade; Gomes, Anderson Humberto; Coelho, Bernardo Cardoso Pinto; Fonseca, Wagner Vieira da (Scientific Journal of the Foot & Ankle, 2018)
Objective: The purpose of this study is to present the surgical outcomes of twelve patients undergoing arthroscopic subtalar arthrodesis using two lateral portals (anterior and medial) in the sinus tarsi. Methods: A retrospective study was conducted with twelve patients (7 men and 5 women) with a mean age of 55.1 (36-74) years who underwent arthroscopic subtalar arthrodesis through the sinus tarsi between May 2015 and December 2016. The post-surgical follow-up was 12 months. Consolidation time and postoperative complications were evaluated, and a validated functional questionnaire from the American Orthopedic Foot and Ankle Society (AOFAS) and the visual analog scale (VAS) for pain were applied both before and after surgery. Results: The mean bone fusion time was 11.5 weeks. Bone consolidation was observed in all analyzed patients. Four patients developed late complications, three of which were related to screw positioning in the calcaneus, while one was related to residual hindfoot varus deformity. Screw-related complications are common with all subtalar arthrodesis techniques, and such complications are considered less relevant when evaluating the effectiveness of the presented technique. The mean preoperative AOFAS score was 42.3 (27-66) points, while the mean postoperative score was 83 (73-94) points. The mean preoperative VAS score for pain was 8.1 (5-10) points, and the mean postoperative score was 2.1 (0-5) points. The above data are similar to those reported in other published studies and reflect high bone consolidation rates. Conclusion: Arthroscopic subtalar arthrodesis through two lateral portals in the sinus tarsi is a safe and effective technique for the treatment of primary and secondary disorders of the subtalar joint. Correct positioning of screws and hindfoot alignment must be carefully ensured to avoid complications related to the synthesis material and hindfoot varus deformity. Level of Evidence IV; Therapeutic Studies; Case Series.